Molecular Interaction Mechanism between 2-Mercaptobenzimidazole and Copper-Zinc Superoxide Dismutase - Teng, Yue; Zou, Luyi; Huang, Ming; Chen, Yadong (PLOS ONE, 2014)
2-Mercaptobenzimidazole (MBI) is widely utilized as a corrosion inhibitor, copper-plating brightener and rubber accelerator. The residue of MBI in the environment is potentially harmful. In the present work, the toxic interaction of MBI with the important antioxidant enzyme copper-zinc superoxide dismutase (Cu/ZnSOD) was investigated using spectroscopic and molecular docking methods. MBI can interact with Cu/ZnSOD to form an MBI-Cu/ZnSOD complex. The binding constant, number of binding sites and thermodynamic parameters were measured, which indicated that MBI could spontaneously bind with Cu/ZnSOD with one binding site through hydrogen bonds and van der Waals forces. MBI bound into the Cu/ZnSOD interface of two subdomains, which caused some microenvironmental and secondary structure changes of Cu/ZnSOD and further resulted in the inhibition of Cu/ZnSOD activity. This work provides direct evidence at a molecular level to show that exposure to MBI could induce changes in the structure and function of the enzyme Cu/ZnSOD. The estimated methods in this work may be applied to probe molecular interactions of biomacromolecules and other pollutants and drugs.